(3bUjOI aj eOM GdfHj Udi Gddg Ydjg hSdes - (3Ge gGfjA , aGNJI HfJ CHj WGdH Hf YHO GdeWdH GdgGTejIs
(3ChdgG (B:s
(3eG ddeSGcjf eKdj ecKQj GdRdd EdG TaGYI NjQ GdNdb hGdQSd s
(3BNQgG (B:s
(3Ke GdUdGI Ydi GdeNJGQ SjOfG gh GdTajY ZOkG aj SGFQ GdCee s
(3Vef eLehY , JQJjHgG (B: (3ef U (B484 - (3U(B485s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B126s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3c (B644) s
Keywords: (3GdCOHs